The Dynamic of Regional Trade Specialisation Pattern in Romania - Oana Ancuta Stangaciu (CES Working Papers, 2011)
The paper analyses the evolution of the regional trade specialization pattern in Romanian regions, by studying the dynamic of their comparative advantages over the period 2000 - 2009. The study finds that, in almost all regions (exceptions are North-East and South-East Region) the international specialization has increased for products in which regions were initially relatively less specialized and has decreased for those in which they were initially highly specialized. Finally, most regions recorded large respectively small specialization improvements in products for which the internal respectively external demand expanded at the fastest rate over the time.
Keywords: 330; FOB exports; CIF imports; Lafay index; comparative advantage; sections of the Combined Nomenclature (CN) Romania